A Research on the Islamic Pottery An Introduction and Critical Review on the Book of The Pottery Known as Kūbāchi - Majid Montazer Zohori; Hossein Sedighian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Pottery is one of the most prominent aspects of Islamic crafts which flourished in both production and decoration. According to the archaeological pieces of evidence the Kūbāchi wares have been spread from Khorasan to Tabriz and it ever-known centers of production were Isfahan, Kerman, Neyshabur, Mashhad and Tabriz. The book of “The Pottery Known as Kūbāchi” is the newest and the possibility most prominent written source about this subject, which argues the archaeological aspects of these wares. This paper aims to introduce the book and review its structure and contents. The first step of review had been started with structural aspects and the process of the narration, and then the content. One of the strengths of this book is the concentration on the various archaeological aspects of this type of pottery. Besides, it can be mentioned that the book could be more attractive to the audience if the documentation and references were more precise. There are some other deficiencies in the typology and categorizing the potteries, those can be edited by the author.